Psihološki motivi za ukvarjanje s fitnesom - Vučković, Vojko (Šport (Ljubljana), 2022)
Researching the motivation for exercise is an important aspect that affects participation in sports centres. We have done an overview of research resources that looked at the relationship between motivation and sports exercise in the fitness industry. The motives for engaging in fitness training can be intristic and extrinsic. Beginners enroll in fitness mainly because of external motives related to appearance and social recognition, but over time their reasons for engaging in sport become a concern for health and well-being, which are intristic motives. We looked for differences in motivation according to the type of exercise that the individual attends; age; gender and BMI. We also wanted to know if there is any impact that social media has on individuals‘ motivation for exercise in fitness. We also found that the wrong motives for exercise can have undesirable results.
Keywords: fitnes; motivacija; psihološki vidik; samopodoba; šport